ULTRASTRUCTURAL CHANGES IN THE SKIN WITH THE INTRODUCTION OF SILVER NANOPARTICLES - Syrma, O.I.; Dumbrova, N.E.; Molchanyuk, N.I.; Ulyanov, V.A.; Skobeeva, V.M. (World of Medicine and Biology, 2014)
The aim was to investigate the ultramicroscopic changes in the skin of rats when administered silver nanoparticles. Used spherical nanoparticles of 30 nm synthesized by citrate method. The experiment was conducted on 17 Wistar rats. After subcutaneous administration of silver nanoparticles solution 0,01ml effect was estimated at 7, 14 days. For electron microscopic examination of skin fragments back fixed, ultrathin sections contrasted by method of Reynolds. Sections were photographed in the electron microscope PЭM-100-01. It is shown, that the introduction of silver nanoparticles occurs only complex reactive changes, which leads to increased protein synthesizing functions of fibroblasts and epithelial cells of the basal layer of the epidermis, the violation of fibro-architectonics and neocollagenogenesis.
Keywords: nanoparticles of silver; skin; transmission electron microscopy